Insulin resistance in transgender individuals correlates with android fat mass. (January 2021) - Bretherton, Ingrid; Spanos, Cassandra; Leemaqz, Shalem Y.; Premaratne, Gehan; Grossmann, Mathis; Zajac, Jeffrey D.; Cheung, Ada S.
Background: Transgender individuals receiving gender-affirming hormone therapy (GAHT) are at increased risk of adverse cardiovascular outcomes. This may be related to effects on body composition and insulin resistance. Aims: To examine relationships between body fat distribution and insulin resistance in transgender individuals on established GAHT. Methods: Comparisons of body composition (dual energy X-ray absorptiometry) and insulin resistance [Homeostasis Model of Insulin Resistance (HOMA2-IR)] were made between transgender individuals (43 trans men and 41 trans women) on established GAHT (>12 months) and age-matched cisgender controls (30 males and 48 females). Multiple linear regressions were used to examine the relationship between HOMA2-IR and fat mass with gender, adjusting for age and total duration of GAHT and Pearson correlation coefficients are reported. Results: Compared with control cisgender women, trans men had mean difference of +7.8 kg (4.0, 11.5), p  < 0.001 in lean mass and higher android:gynoid fat ratio [0.2 (0.1, 0.3), p  < 0.001], but no difference in overall fat mass or insulin resistance. Compared with control cisgender men, trans women had median difference in lean mass of −6.9 kg (–10.6, –3.1), p  < 0.001, fat mass of +9.8 kg (3.9, 14.5), p  = 0.001, lower android:gynoid fat ratio −0.1 (–0.2, –0.0), p  < 0.05), and higher insulin resistance 1.6 (1.3–1.9), p  < 0.001). Higher HOMA2-IR correlated with higher android ( r 2  = 0.712, p  < 0.001) and gynoid ( r 2  = 0.572, p  < 0.001) fat mass in both trans men and trans women. Conclusion: Android fat more strongly correlates with insulin resistance than gynoid fat in transgender individuals. Higher fat mass and insulin resistance in trans women may predispose to increased cardiovascular risk. Despite adverse fat distribution, insulin resistance was not higher in trans men.